DIFFERENCES IN INTERFERON GAMMA LEVELS IN TREATMENT OF TUBERCULOSIS IN INTENSIVE PHASE AND ADVANCED PHASE - SY. Didik Widiyanto; Ririh Jatmi Wikandari; Wiwit Sulistyasmi; Kuncara, Rachmad Bayu (Jurnal Biosains Pascasarjana, 2024)
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis complex (MTBC). Anti-tuberculosis drugs given to active TB sufferers consist of 3 or 4 combinations. Tuberculosis treatment is divided into intensive phase treatment (2 weeks) and continuation phase (16 weeks / 4 months). Interferon gamma (IFN Î³) is a protein belonging to the cytokine family which plays a role in eliminating MTB bacteria through a cell-mediated immunity mechanism. The aim of this study was to analyze differences in gamma interferon levels in the intensive phase and advanced phase of tuberculosis treatment. This research method is an analytical observational study with a cross-sectional design (cross sectional study). The research design used was a randomized post test only control group design. Data were analyzed using the Kruskal Wallis test with statistical test results obtained with a p value of 0.033 (> 0.05), meaning there was a difference in IFN Î³ levels in the intensive phase and advanced phase of tuberculosis treatment.